Potential of Flavonoid in Mahkota Dewa to Reduce Sistolic and Diastolic Blood Pressure in Patient with Hypertension - Abed Nego Okhtara (Universitas Airlangga, 2020)
Treating hypertension by using antihypertensive drugs and diuretics has many harmful side effects. Mahkota Dewa fruit can be used as alternative treatment with minimal side effects. As generallly known that blood pressure increases slowly with age, which makes hypertension a critical disease to the elderly. This disease could be treated using flavonoid compounds that is contained in Mahkota Dewa fruit because it is effective in reducing blood pressure.